Verification of a novel measuring method for determining pre- and postoperative leg length in the context of total hip arthroplasty: a technical feasibility study. (17th November 2018) - Schmidt, Michael; Prietzel, Torsten; Wendler, Toni; Möbius, Robert; Schleifenbaum, Stefan; Hammer, Niels; Grunert, Ronny
Abstract: Following total hip arthroplasty (THA), leg length can easily be modified, for example by different-sized endoprosthetic components. Currently, precise reconstruction depends mainly on the assessment of the surgeon. The aim of this study was to determine the accuracy of a new optical measuring system (OMS) using a novel measuring method capable of determining changes in leg length. Measurements with different investigators on an artificial leg and under clinical conditions were carried out. Measurements under clinical conditions were accomplished with a human body donor before and following prosthetic hip implantation. Furthermore, computed tomography (CT) was used to compare the function and the precision of the OMS relating to established measuring methods. The following results were achieved. The overall mean result of preoperative leg length determination by the OMS was 775.3 ± 5.8 mm (CT: 786.4 mm). The overall mean result of postoperative leg length determination by the OMS was 776.9 ± 10.8 mm (CT: 795.0mm). Measurements carried out showed that the novel measuring method works in principle. However, the viable prototype based on it has a lower accuracy compared to CT-based reference measurements, indicating the necessity of integrating more precise hardware.